(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
This study examined the environmental effects of oil spillage in Nembe, Bayelsa State by determining the particle size distribution of the soil, determining the nutrients composition of the soil contaminated with oil spill and the soil of a nearby control site in the study area, comparing the composition of the soil from the polluted site and that from the control site, and comparing the heavy metal present in the polluted soil in the study area with the NESREA standards. The study adopted laboratory research design in generating data for the analyses. Ten samples each were collected from two communities in Nembe, Okoroba and Etieme both from top soils and at depth. From the analyses it was found that there is a slight but insignificant variation on the pH of the soils, which averaged from the (top soil) 6.12 and 5.73 for the control Etieme and the affected soil of Okoroba respectively. The soils are all slightly acidic and this acidity cannot be attributed entirely to the oil spill since the control is equally acidic. Soil gotten from the top at Okoroba had a loamy sand (LS) texture. This has a a high proportion of sand, while the sub soil gotten from the same location had a silt loam (SL) texture, with a balanced mixture of s and, silt and clay. Soil gotten from the top at Etieme had a silt loam texture while the subsoil had a silt clay loam texture(SCL), which contain a high proportion of clay compared to sand and silt. This fraction averaged 66.72% in Etieme soil and 76.72% in Okoroba soil while clay decreased from 21% in Etieme to 16.70 in Okoroba. From the test of hypothesis, it was found that the oil spill concentration of the soil in the polluted site and the soil in the control site are not significantly different from each other; also the heavy metal concentration of the soil in the polluted site did not significantly deviate from the NESREA standards. Nevertheless, it should be known that heavy metals have the ability to bio-accumulate and biomagnify, hence the metal concentrations of this site will come to deviate from that of the NESREA standards over time if precautionary measures are not taken. It was also confirmed that oil spill has detrimental effect on both man and his environment. Comparison of the analytical data gotten from the polluted soil with the data gotten from the control nearby soil shows that there was no significant difference between the soil nutrient in the polluted site and the soil in the control site. The study therefore concluded that effect of oil spill on land as an aspect of the environment in Nembe is still minimal hence the need to urgently tackle the problem of oil spill was recommended so as to nip these negative effects by the bud before it goes out of hand.